Evaluation of anti-malarial drugs' use in Fitche Hospital, North Shoa, Oromia Region, Ethiopia - Rosa Getachew; Wote Amelo; Eshetu Mulisa Bobasa (Wolters Kluwer Medknow Publications, 2016)
Objective: Retrospective evaluation of anti-malarial drugs' use in Fitche Hospital, North Shoa, Oromia Region, Ethiopia. Methods: Retrospective cross-sectional study design was conducted using selected patients cards of 1-year (January 2012-January 2013 G.C) with anti-malarial agents from January 18 to 30, 2013. The sample size was calculated by using Joint Commission on the Accreditation of Health care Organization criteria and sampling was done by using a systematic random sampling technique. Results: One hundred and twenty-five patient cards with anti-malarial drugs were reviewed of which 32.8%, 21.6%, 15.2% belongs to age range of 20-29, 10-19, and 30-39, respectively. Chloroquine prescription accounts for 50.4% from total anti-malarial drugs. 71.2% and 78.4% of patients received antibiotics and analgesics, respectively, with anti-malarial drugs. 77.6% of drugs were prescribed by generic name while the brand name was 22.39%. Conclusions: The study done in Fitche Hospital revealed that the use of anti-malarial agent was not in complete agreement with the current guideline of Ethiopia despite good practice.